Efficacy of Probiotics as Adjunctive Therapy to Nonsurgical Treatment of Peri-Implant Mucositis: A Systematic Review and Meta-Analysis - Zhao, Rui; Hu, Huimin; Wang, Yan; Lai, Wenli; Jian, Fan (Frontiers in Pharmacology, 2021)
Background: Peri-implant mucositis (PiM) is an inflammation of the soft tissues surrounding the dental implant and is the precursor of the destructive inflammatory peri-implantitis. PiM is usually reversible, but difficult to eradicate. Mechanical debridement (MD) is the conventional procedure to treat PiM although not enough to reach a complete resolution. Recently, probiotics have been investigated in the treatment of peri-implant disease. Therefore, the aim of this systematic review and meta-analysis was to investigate the efficacy of the probiotic therapy combined with MD compared with MD alone or MD+placebo in patients with PiM. Methods: A search using electronic databases and a manual search were performed up to November 2019 and included randomized controlled trials comparing MD + probiotic versus MD. Probing depth reduction was selected as the primary outcome and the weighted mean difference in probing depth reduction was evaluated in a random effect model. Results: Five eligible publications were included in this systematic review and four in the meta-analysis. At the implant level, the weighted mean difference in the probing depth reduction between the test and control group was -0.12 mm [95% CI (-0.38, 0.14), P=0.38], thus meaning that the adjunctive probiotic therapy was not improving PiM compared with MD alone or MD+placebo. The meta-analysis also showed no statistically significant results in the secondary outcomes (reduction of full mouth plaque index and full mouth bleeding on probing, absence of bleeding on probing at implant level, and microorganism load). Conclusion: The findings of this systematic review and meta-analysis suggested that the adjunctive use of probiotics did not improve the efficacy of MD in PiM treatment in clinical and microbial outcomes, at least in a short-term.